A Comparative Study between TPS and LRD Strategy to Enhance Students’ Reading Comprehension - Tampubolon, Apricia; Panjaitan, Nelson Balisar (LPPM Universitas Advent Indonesia, 2019)
The purpose of this study is to find out if there is any significant difference in students’ reading comprehension enhancement between those who were taught using Listen-Read-Discuss strategy and those who were taught using Think-Pair-Share strategy. This study is a quantitative research method using comparative design by using pre-test and post-test. This study was designed to find out the answer to the following question: Is there any significant difference in students’ reading comprehension enhancement between those who were taught by Think-Pair-Share strategy and those who were taught by Listen-Read-Discuss strategy. The sample of this study was two classes of grade VIII SMPN 10 Cimahi, Bandung. Grade VIII F was taught using Think-Pair-Share and grade VIII was taught using Listen-Read-Discuss. The instrument used for this study was a reading comprehension test, which contained 39 multiple-choice questions. The result of this study showed from the mean score that both classes had an enhancement in their reading comprehension. In addition, there was no significant difference between those who were taught using TPS and those who were taught using LRD strategy. However, it meant that both strategies were efficient in enhancing students’ reading comprehension.